Self-Efficacy, Perceived Organizational Support, and Organizational Citizenship Behavior: The Mediating Effect of Organizational Culture - Poniasih, Ni Komang Putri; Sapta, I Ketut Septia; Widnyana, I Wayan; Laksemini, Kadek Dewi Indah Sri (Yayasan Riset dan Pengembangan Intelektual, 2025)
The Village Office is required to have employees who have extra roles, good personalities, and have a high commitment to the agency so that the company's goals can be achieved. One of the factors that influence organizational citizenship behavior is self-efficacy and perceived organizational support. This study aims to provide comprehensive insight into the factors that influence organizational citizenship behavior with a focus on aspects of self-efficacy and perceived organizational support, and how organizational culture can mediate these influences. The research design used in this study is a quantitative approach. The results of the study indicate that self-efficacy and perceived organizational support have a positive and significant effect on organizational culture at the Bongan Tabanan Village Office. Self-efficacy, perceived organizational support, and organizational culture have a positive and significant effect on Organizational Citizenship Behavior at the Bongan Tabanan Village Office. Organizational culture is able to mediate the influence of self-efficacy and perceived organizational support on Organizational Citizenship Behavior at the Bongan Tabanan Village Office. This means that an increase in self-efficacy and perceived organizational support will improve organizational culture and will also improve Organizational Citizenship Behavior at the Bongan Tabanan Village Office.